2018
DOI: 10.1007/s40273-018-0653-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Crohn’s Disease Treatment with Vedolizumab and Ustekinumab After Failure of Tumor Necrosis Factor-α Antagonist

Abstract: ObjectiveThe aim was to evaluate the cost-effectiveness of Crohn’s disease (CD) treatment with vedolizumab and ustekinumab after failure of therapy with tumor necrosis factor-α antagonists (anti-TNFs).MethodsThe Markov model incorporated the lifetime horizon, synthesis-based estimates of biologics’ efficacy in relation to anti-TNF exposure, and administration of biologics reflecting clinical practice (e.g., sequence of biologics, retreatment, 12-month treatment). The utilities, non-medical costs and indirect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The major limiting factor to ustekinumab use is cost, although a recent study has shown that its use after failure of anti‐TNF therapy is cost‐effective at a threshold of €31 500 ($35 743), leading to a gain of 0.349 quality‐adjusted life years (QALYs) at an additional cost of €6593.82 ($7481) 28 . By this evaluation, the use of ustekinumab for the majority of patients in this review, who had failed several anti‐TNF medications for treatment of their IBD‐associated cutaneous disease, was cost‐effective.…”
Section: Discussionmentioning
confidence: 99%
“…The major limiting factor to ustekinumab use is cost, although a recent study has shown that its use after failure of anti‐TNF therapy is cost‐effective at a threshold of €31 500 ($35 743), leading to a gain of 0.349 quality‐adjusted life years (QALYs) at an additional cost of €6593.82 ($7481) 28 . By this evaluation, the use of ustekinumab for the majority of patients in this review, who had failed several anti‐TNF medications for treatment of their IBD‐associated cutaneous disease, was cost‐effective.…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis of ustekinumab’s cost-effectiveness versus vedolizumab as a third line agent after failure with two TNF-alpha inhibitors found that vedolizumab had higher costs of $168,648 as well as a larger QALY gain of 0.029, resulting in an ICER of $5,815,448 [ 69 ]. A polish study found treatment with ustekinumab after failing one TNF-antagonist associated to a QALY gain of 0.349 and an ICER of €18,878 compared to adalimumab after infliximab failure [ 28 ]. The variations in outcomes of cost-effectiveness analyses of biologics in CD emphasise the importance of further research in the field, and a need for a greater consensus over model design and assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, properly modelling treatment sequences would require currently unavailable efficacy data, or ill-founded assumptions. Although the model allows for maintenance transitions from the moderate to severe health state, the structure does not capture increased relapse risk after discontinuing biologics [ 28 , 72 , 73 ], and—as previously discussed—does not consider the impact of surgery on future surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis has shown that, after the failure of an anti-TNF α, the probability of remission using a second anti-TNF α substantially decreases, and the efficacy of the second anti-TNF α clearly depends on the reason for switching treatment, with the highest remission rates for patients with drug intolerance (61%) and the lowest for patients with PNR (30%) or LOR (45%) [47] . Therefore, a sensible approach after the failure of the first anti-TNF α could be to switch to another biologic with a different mode of action [48] , especially in IBD patients with PNR or LOR [49 , 50] . Nevertheless, therapeutic drug level monitoring, when available, may be useful in guiding decisions related to the type of biologic to use after the failure of the first anti-TNF α.…”
Section: Article In Pressmentioning
confidence: 99%